Study on Incentive Price of Fermented Cocoa to Overcome Reluctance of Farmer to Apply Fermentation : Case Study in Jembrana Regency - Joko Soemarno; Yuli Hariyanti; Soetanto Abdoellah Soeparto; Diany Faila Sophia Hartatri (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Improving cocoa quality through encouraging farmers to do fermentation is one of the ways to increase the added value of cocoa. However, majority ofIndonesian farmers are reluctance to do fermentation. This research aimed to study factors causing farmers reluctant to do fermentation, weight differencebetween fermented and unfermented cocoa, cocoa processing time difference between fermented and unfermented cocoa, quality difference between fermentedand unfermented coco refers to cocoa bean standard (SNI): 01-2323-2008/Amd-2010, and feasible added value incentive of fermented cocoa beans. The data collectionwere conducted through household farmers’ survey, focus group discussion and experimental research. The experimental research was conducted to understandthe weight and processing time differences; and to asess the quality, including moisture content, bean count, pH and fermentation index. Analysis of the datawere conducted by methods of Fishbone Ishikawa and logit multiplier linear analysis. The research results showed that the main factors causing farmers reluctant todo fermentation were insuitable of selling price of fermented cocoa, the existence of village collectors in buying unfermented cocoa, the lack of cooperation amongfarmers in farmer group (Subak Abian) and the lack of farmers’ skills on cocoa bean fermentation. This study also found that the weight depreciation differencebetween fermented and unfermented cocoa was 0.5-3.75%, and the processing time difference between fermented and unfermented cocoa was 12-24 hours. Qualityof fermented cocoa beans was higher than that of unfermented cocoa beans and it can fulfill the standard of SNI: 01-2323-2008/Amd-2010. It was found that thefeasible added value incentive of fermented cocoa benas was 2,126-3,426 IDR/kg. Keywords: cocoa, fermentation, unfermented, quality, incentive